Pengaruh Religiusitas terhadap Intensi Boikot Mahasiswa UI untuk Produk Terafiliasi Israel - Fauzi, Muhammad Haiqal; Azzahra, Rifkanissa; Nirwasita, Raditya Akhdan; Izzan, Muhammad (Jurnal Manajemen dan Usahawan Indonesia, 2024)
This study aims to analyze the factors influencing students at Universitas Indonesia (UI) in participating in the boycott movement against products affiliated with Israel. Data were collected through an online survey of 408 UI students from the 2021–2024 cohorts. The sample was selected using the purposive sampling method. Analysis using Covariance-Based Structural Equation Modeling (CB-SEM) demonstrates that anger, empathy, and subjective norms have a positive and significant impact on boycott intentions, while religiosity is not significant. Economic threats are found to increase anger, which in turn drives boycott intentions. These findings emphasize that emotional factors and social pressure play a more dominant role in boycott participation decisions compared to religiosity. The study implies that campaigns highlighting economic impacts and humanitarian issues can enhance boycott participation. Social organizations and relevant institutions are advised to leverage social media to strengthen social norms supporting this movement. Future research should expand the sample scope and consider additional factors, such as political influence or media roles.